DAMPAK PERKEMBANGAN PARIWISATA TERHADAP EKONOMI MASYARAKAT KOTA MALANG TAHUN 2015-2019 (Universitas Kristen Satya Wacana, 2022)
Malang city is one of the cities that has the potential in the field of tourism. The existence of tourism is expected to improve the economy of the community. The purpose of this research is to find out the impact of tourism development on the economy of the Malang people in 2015-2019. The method used in this research is descriptive with quantitative analysis techniques. Data analysis techniques used in this study are multiple linear regression. Based on the results of the study showed that the city of Malang has 78 tourist attractions that consist of various types of tourism, and the economy of Malang city increased from 2015-2019 when viewed from the variable gross regional domestic income (GDP). Besides, the large number of tourists affect income, so the greater number of tourists, the higher the revenue, and vice versa. Unlike the variable amount of transportation, this variable does not affect income.